Qatar : 2018 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Qatar. (IMF Staff Country Reports; Country Report, 2018)
This 2018 Article IV Consultation highlights that Qatar's growth performance remains resilient. The direct economic and financial impact of the diplomatic rift between Qatar and some countries in the region has been manageable. Nonhydrocarbon real GDP growth is estimated to have moderated to about 4 percent in 2017 owing to on-going fiscal consolidation and the effect of the diplomatic rift. Headline inflation remains subdued, primarily owing to lower rental prices. The near-term growth outlook is broadly positive. Overall, GDP growth of 2.6 percent is projected for 2018. Inflation is expected to peak at 3.9 percent in 2018 before easing to 2.2 percent in the medium term. The underlying fiscal position continues to improve.